2013
DOI: 10.1021/jm400898x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Piperidyl-1,2,3-Triazole Ureas as Selective Chemical Probes of Endocannabinoid Biosynthesis

Abstract: We have previously shown that 1,2,3-triazole ureas (1,2,3-TUs) act as versatile class of irreversible serine hydrolase inhibitors that can be tuned to create selective probes for diverse members of this large enzyme class, including diacylglycerol lipase-β (DAGLβ), a principal biosynthetic enzyme for the endocannabinoid 2-arachidonoylglycerol (2-AG). Here, we provide a detailed account of the discovery, synthesis, and structure-activity relationship (SAR) of (2-substituted)-piperidyl-1,2,3-TUs that selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 30 publications
4
60
0
Order By: Relevance
“…3 C and G) displayed greater inhibitory potency at DAGLα than DAGLβ. Both compounds exhibited good selectivity against other serine hydrolases including MAGL and FAAH but showed cross-reactivity with ABHD6, as expected (20)(21)(22). To identify appropriate negative control probes, we confirmed that the ABHD6-selective inhibitors KT185 (Fig.…”
Section: Resultssupporting
confidence: 66%
“…3 C and G) displayed greater inhibitory potency at DAGLα than DAGLβ. Both compounds exhibited good selectivity against other serine hydrolases including MAGL and FAAH but showed cross-reactivity with ABHD6, as expected (20)(21)(22). To identify appropriate negative control probes, we confirmed that the ABHD6-selective inhibitors KT185 (Fig.…”
Section: Resultssupporting
confidence: 66%
“…S1C and Dataset S1), whereas the 40+ other serine hydrolases detected by ABPP were unchanged. Selective loss of DDHD2 in DDHD2 −/− mice was further verified using DDHD2-directed (HT-01) and broad-spectrum [FP-rhodamine (FP-Rh)] fluorescent activity-based probes (17), where the former probe revealed the absence of a characteristic 75-kDa DDHD2 doublet (9) in DDHD2 −/− brains, whereas other serine hydrolase signals were unaltered (Fig. 1C).…”
Section: Resultsmentioning
confidence: 78%
“…S11A). Higher resolution, quantitative MS analyses using the ABPP-stable isotope labeling by amino acids in cell culture method (17) confirmed that KLH45 (25 nM, 4 h) completely inactivated DDHD2 (>95% inhibition) in Neuro2A cells and showed no cross-reactivity with any of the other 40+ detected serine hydrolases with the exception of ABHD6 (SI Appendix, Fig. S11B and Dataset S2).…”
Section: Triglyceride (Tag) Accumulation In Ddhd2mentioning
confidence: 83%
See 1 more Smart Citation
“…A thin layered chromatography based radio-assay involving radio-labelled DAG has also been utilized to measure DAGL activity 2,28 . Several fluorescently labelled activity based probes with applications in gel based assays have been developed for the DAGLs, ranging from the generic serine hydrolase binding probe -fluorophosphonate 27 to more recent probes with ever improving selectivity for DAGLα and DAGLβ 13, 29,30 . Recently, higher throughput assays suitable for drug-discovery programs for the DAGLs have been reported.…”
Section: Introductionmentioning
confidence: 99%